Effects of fermented ramie feed on the growth performance, serum biochemistry, metabolic capacity, antioxidant capacity, and intestinal health of Linwu ducks - Lv, Zonghao; Zhang, Jingmeng; Li, Cong; Li, Zhen; Zhang, Zhizhong; Lv, Biguang; Cheng, Xuan; Zhao, Haohan; Chen, Qinghua; Lin, Qian (Frontiers in Veterinary Science, 2025)
This study investigated the effects of fermented ramie feed (FRF) on the growth performance, serum biochemistry, metabolic capacity, antioxidant capacity, and intestinal health of Linwu ducks. A total of 480 female Linwu ducks (age: 28 days) were randomly divided into five treatments (six replicates per group; 16 ducks per replicate). The control group received a basal diet and the treatment groups received the basal diet supplemented with by 3%, 6%, 9% or 12% FRF. The experiment lasted 21 days. Notably, 3% and 6% FRF trended to increase the final body weight (P = 0.097) and significantly increased the thymus index (P < 0.05). Regarding serum indices, FRF greatly reduced the triglyceride and glucose contents, and increased the catalase and glutathione peroxidase activities (P < 0.05). Besides, FRF significantly increased the apparent metabolic rates of dry matter, crude protein, crude ash and gross energy (P < 0.05). Furthermore, FRF remarkably improved villus height in the duodenum. FRF also increased the relative abundances of beneficial bacteria (Alistipes and Barnesiella) and reduced the relative abundances of harmful parasitic bacteria (Desulfovibrio and Enterenecus) in the cecum (P < 0.05). Thus, partial FRF substitution greatly improved serum biochemistry, antioxidant capacity, metabolic capacity and intestinal health in Linwu ducks, thereby enhancing the growth performance to a certain extent. The optimal level of FRF substitution is 3%−6% according to the impacts of growth performance and overall health.